Efficacy of intradermal hyaluronic acid plus polynucleotides in vulvovaginal atrophy: a pilot study. (3rd September 2022) - Angelucci, M.; Frascani, F.; Franceschelli, A.; Lusi, A.; Garo, M. L.
Abstract: Objective: This study aimed to evaluate the safety and efficacy of vulvovaginal intradermal injections of polynucleotides (PN) combined with hyaluronic acid (HA) in postmenopausal women affected by vulvovaginal atrophy (VVA). Materials and methods: Postmenopausal women affected by VVA were treated with vulvar and vaginal intradermal injections of one prefilled syringe of 2 ml PN/HA every 2 weeks for four sessions. Patients were evaluated at T0 (baseline), T1 (after session 4) and T2 (1 month after session 4). Evaluation of the treatment was assessed by three international validated questionnaires: Vaginal Health Index (VHI), Vulvar Health Index (VuHI) and Female Sexual Function Index (FSFI). The Wilcoxon matched-paired signed-rank test was used to compare the differences in VHI, VuHI, FSFI and FSFI domains within the groups. Statistical significance was set at p < 0.05. Results: Fifty patients were included in the study (mean age 59.9 ± 7.6 years). Overall, the VHI, VuHI and FSFI reported statistically significant differences between baseline and T1 ( p < 0.001) and between baseline and T2 ( p < 0.001). All FSFI domains registered a statistically significant increase between baseline and T2 ( p < 0.001). No complications or side effects were observed. Conclusions: Vulvovaginal intradermal injection of PN/HA is a safe, effective treatment, is not expensive and is a reproducible procedure in postmenopausal women with VVA.